Implementation of Test Suites using Enhanced State Chart Diagrams: A Case Study - Gupta, K.; Goyal, P. (Journal of Scientific Research, 2023)
An essential part of software engineering is testing. A series of pre-testing tasks should be completed before performing testing tasks. Implementing test suites is one of the pre-testing phases. In this work, a case study has been used to implement the suggested method for implementing test suites. The strategy is based on an analysis of UML (Unified Modelling Language) enhanced state chart diagrams (SCDs). UML state chart diagram analysis, AD (activity diagram) conversion into a graph, AG (activity graph) simplification, and test suite implementation are all steps in the generating process.